Incompressible flow through choke valve: An experimental and computational investigation. (August 2022) - Gabel, Trevor; Mitra, Harsa; Williams, Dan; Koeck, Frank; Mónico, Rodolfo Ostilla; Alba, Kamran
Abstract: The flow within a control valve is complex, particularly for choke types with multiple entries. Despite the abundant use of control valves in pressure-reduction applications across various fields, there is lack of understanding of fluid flow behavior within such valves. Failure associated with vortex shedding and Flow-Induced Vibration (FIV) remains as a long-standing issue with operation of control (choke) valves. This industry-academia collaborative study constitutes a coupled computational and experimental methodology to analyze the complex flow within a choke valve under laminar inflow conditions. The investigation is conducted on a control valve, currently used in industry, at four specific choke positions. Incompressible Computational Fluid Dynamics (CFD) simulations are performed using water as fluid and Detached Eddy Simulation (DES) as turbulence model under two different laminar inlet flow rate (equivalent Reynolds number, Re, approximately 100 and 500). Experiments are carried out under the same conditions using Particle Image Velocimetry (PIV). The instantaneous and time-averaged (mean) vorticity and velocity contours are presented on four selected planar cross sections providing complementary information on the flow physics. Despite the complex geometry of the choke valve in question as well as the fluid flow developing within it, close agreement is found between the computational and experimental results. Both the studies reveal that, at low valve openings, when only the small ports are engaged, there forms a four-lobed vortical structure which is established upon collision of the incoming jets. The vortical structure of the flow is much more complex at higher valve openings when both the small and large ports are engaged. The inherent unsteadiness associated with turbulent flow within the valve chamber leads to flipping motion of the formed jets and vortex shedding; mechanisms of which are explained in detail in the paper. The frequency spectrum of the fluid flow is correspondingly assessed using Fast Fourier Transform (FFT) examining the dominant vibration modes and corresponding Strouhal numbers. The dominant frequency peaks found in computational and experimental studies can result in FIV and resonance failure of control valves in practice. The autocorrelation analysis and continuous wavelet transform have furthermore been augmented in signal processing of the data to illuminate the oscillatory behavior of the flow due to vortex shedding. Highlights: Head-on collision of fluid jets within a complex industry choke valve. Integrated experimental and computational approach to study choke valve flow. Investigating various choke positions and flow rates using CFD and PIV techniques. Signal processing of transient data, in both dimensional and dimensionless spaces.